1996
DOI: 10.1093/schbul/22.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Brief Family Psychoeducation on Self-efficacy

Abstract: One hundred eighty-three relatives of people with serious mental illnesses were randomly assigned to receive individualized consultation or group psychoeducation or were placed on a 9-month wait list. Analysis of variance and multiple regression revealed that the individualized consultation increased the family members' sense of self-efficacy regarding mentally ill relatives. Group psychoeducation was helpful in increasing self-efficacy of family members who had never participated in a support or advocacy grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(43 citation statements)
references
References 34 publications
2
37
0
4
Order By: Relevance
“…A total of 194 patients were randomized with an approximately 20% dropout rate in both conditions. Solomon et al 164 compared individualized family consultation with group family psychoeducation and a third arm that was a waiting list control for relatives of individuals diagnosed with mental disorders with 295 (64%) or 296 (36%) codes (schizophrenia spectrum, major depression, or bipolar disorder). A total of 225 participants were randomized, and 42 dropped out, leaving 183 relatives.…”
Section: Family-based Servicesmentioning
confidence: 99%
“…A total of 194 patients were randomized with an approximately 20% dropout rate in both conditions. Solomon et al 164 compared individualized family consultation with group family psychoeducation and a third arm that was a waiting list control for relatives of individuals diagnosed with mental disorders with 295 (64%) or 296 (36%) codes (schizophrenia spectrum, major depression, or bipolar disorder). A total of 225 participants were randomized, and 42 dropped out, leaving 183 relatives.…”
Section: Family-based Servicesmentioning
confidence: 99%
“…Having the patient present has been shown to have some negative effects on the group process, with relatives in patient-present groups making fewer personal and topic-relevant comments (Reilly, Rohrbaugh, & Lackner, 1988). Previous psychoeducation programs have excluded patients to provide a forum in which the relatives can talk freely (Cozolino et al, 1988;Linszen et al, 1996;Reinares et al, 2004;Solomon et al, 1996). …”
mentioning
confidence: 99%
“…Several studies have demonstrated that family psychoeducation programs can increase knowledge about the illness, increase familial support, reduce family burden, increase selfefficacy, and reduce relapse rates in psychiatric disorders (Abramowitz & Coursey, 1989;Cozolino, Goldstein, Nuechterlein, & West, 1988;Dixon et al, 2000;Honig, Hofman, Rozendaal, & Dingemans, 1997;Pitschel-Walz, Leucht, Baeuml, Kissling, & Engel, 2001;Solomon, Draine, Mannion, & Meisel, 1996). In bipolar disorder, family, couple, and parent psychoeducation programs also have significantly improved nonverbal interactions, caregiver knowledge of the disorder, patient understanding of the illness, positive family interactions, caregiver distress, coping, attributions, patient functioning, and patient medication adherence (Bland & Harrison, 2000;Brent, Poling, McKain, & Baugher, 1993;Clarkin, Carpenter, Hull, Wilner, & Glick, 1998;Fristad, Goldberg-Arnold, & Gavazzi, 2003;Simoneau, Miklowitz, Richards, Saleem, & George, 1999;van Gent & Zwart, 1991).…”
mentioning
confidence: 99%
“…In veel gevallen worden in elk geval de resultaten van de cursus met netwerkleden besproken (zie bijvoorbeeld voor mensen met een manisch depressief syndroom; Vogtla¨nder & Van Gent, 1998 ), of doen de netwerkleden aan een gedeelte van de cursus mee (zie bijvoorbeeld voor mensen met een borderline persoonlijkheidsstoornis; Freije, Dietz, & Appelo, 2002 ). Bij psychotische stoornissen wordt de psycho-educatie vaak geheel samen met de netwerkleden gegeven (zie bijvoorbeeld Solomon, Draine, & Mannion, 1996 ). Samenwerken met 'belangrijke anderen' had een positief effect op de generalisatie van hetgeen tijdens de cursus aan de orde kwam en beı¨nvloedde daarmee de ervaren steun en het zelfvertrouwen.…”
Section: Beschouwingunclassified